(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
With regards to complex monetary relationships, Investment choices, uncertainty/risks, and the repeating financial emergencies, psychological variables have become progressively significant in Investment decision making. Exploration on the investment behavior of various scholars at various times and place, this generally acknowledged interdisciplinary financial field: Behavioral Finance. To understand and explain psychological decision making and investment behavior, it is necessary to study the behavioral factors that affect individual’s mentality. Many researchers have researched the aspects which determine the financial behaviour and their effect on economic judgment, notably with cognitive bias. Traders are frequently not conscious of their biases & preconceptions. If traders are informed of the biases they may confront, they may behave more logically. This mentality can improve the quality of your decision-making. The work aims to help policymakers and investors understand psychological deviations so that people can make better judgments when buying and lower the likelihood of behavior aberrations, since the repercussions of individual mistakes are eventually mirrored on the macro scale, generating stability and Financial and economic crises.